solve the system of equation by using gauss Jordan method
![- 3x + 2y - 6z = 14 \\ 4x - 5y + 2z = - 3 \\ 7x + 9y + 3z = 14 - 3x + 2y - 6z = 14 \\ 4x - 5y + 2z = - 3 \\ 7x + 9y + 3z = 14](https://tex.z-dn.net/?f=+-+3x+%2B+2y+-+6z+%3D+14++%5C%5C+4x+-+5y+%2B+2z+%3D++-+3+%5C%5C+7x+%2B+9y+%2B+3z+%3D+14)
Answers
Answer:
plz mark my answer as brainiest
1)
2)
3)
all ans with step
Step-by-step explanation:
1).
Let's solve for x.
−3x+2y−6z=14
Step 1: Add -2y to both sides.
−3x+2y−6z+−2y=14+−2y
−3x−6z=−2y+14
Step 2: Add 6z to both sides.
−3x−6z+6z=−2y+14+6z
−3x=−2y+6z+14
Step 3: Divide both sides by -3.
−3x
−3
=
−2y+6z+14
−3
x=
2
3
y−2z+
−14
3
Answer:
x=
2
3
y−2z+
−14
3
2). Let's solve for x.
4x−5y+2z=−3
Step 1: Add 5y to both sides.
4x−5y+2z+5y=−3+5y
4x+2z=5y−3
Step 2: Add -2z to both sides.
4x+2z+−2z=5y−3+−2z
4x=5y−2z−3
Step 3: Divide both sides by 4.
4x
4
=
5y−2z−3
4
x=
5
4
y+
−1
2
z+
−3
4
Answer:
x=
5
4
y+
−1
2
z+
−3
4
3). Let's solve for x.
7x+9y+3z=14
Step 1: Add -9y to both sides.
7x+9y+3z+−9y=14+−9y
7x+3z=−9y+14
Step 2: Add -3z to both sides.
7x+3z+−3z=−9y+14+−3z
7x=−9y−3z+14
Step 3: Divide both sides by 7.
7x
7
=
−9y−3z+14
7
x=
−9
7
y+
−3
7
z+2
Answer:
x=
−9
7
y+
−3
7
z+2